The Role of CEO Financial Skills on Company Performance - PRADNYANATA, I Gede Agus; NARINDRA, Anak Agung Ngurah Mayun (PT Keberlanjutan Strategis Indonesia, 2024)
Fast and dynamic economic growth requires companies to choose a chief executive officer (CEO) who has strong technical and managerial skills. One important ability for a company CEO to have is financial expertise. The CEO's financial capabilities can help the company manage resources more efficiently and effectively, especially during times of crisis. This research aims to determine the role of CEO financial expertise on company performance during the Covid 19 pandemic. This research is quantitative in nature using secondary data obtained from the company's annual report and financial statements. The sample for this research was 40 property and real estate companies listed on the Indonesia Stock Exchange in 2020-2022. The data analysis technique used is panel data regression analysis. The results obtained show that CEO financial expertise plays a negative and significant role in company performance. This finding explains that, during the financial crisis, the CEO's expertise was not able to improve company performance.